Apathy and effort-based decision making: a cognitive mechanism underlying amotivated behaviour - Le Heron, C (2018)
Apathy is a common, debilitating but poorly understood disorder of motivation that manifests in reduced goal directed behaviours. The integration of cost and reward information about potential actions is central to normal motivated behaviour. This thesis will argue that disruption of this normal process – often termed effort-based decision making – underlies the clinical syndrome of apathy. Two broad sets of questions are investigated to address this hypothesis, in clinically apathetic patients with either Parkinson’s disease (PD) or a genetic form of cerebral small vessel disease (SVD). Firstly, are apathetic patients hypersensitive to effort costs, or insensitive to rewards when making decisions about potential actions? Do these changes associated with apathy map onto physiological alterations in reward processing and disruption of anatomical regions that underlie normal effort-based decision making? And do these behavioural changes occur along the same axis as those induced by dopamine depletion? Secondly, using an ecological framework of decision making in which participants must compare current (foreground) reward information to the background reward context to guide adaptive behaviour, this research explores whether apathy is associated with aberrant use of background reward information, and how this interacts with the dopaminergic system. The studies demonstrate effort-based decision making is disrupted in patients with apathy, driven by reduced incentivisation by the rewarding outcomes of actions rather than hypersensitivity to effort costs themselves. Reward insensitivity manifests in both behavioural choices and physiological responses to incentives, is associated with reduced white matter integrity in tracts connecting regions crucial for effort-based decision making, but occurs along a separate mechanistic axis to changes induced by dopamine depletion. Furthermore, whilst healthy human decision makers are remarkably sensitive to changes in background reward environment, apathy changed the influence of this information – dependent on dopaminergic tone. Together, the work in this thesis presents evidence that disruption of a specific cognitive process underlies the apathetic syndrome. This advances understanding of normal motivated behaviour and identifies potential therapeutic avenues to treat this important clinical syndrome.